Storage of Actinobacteria of the Genera Streptomyces and Nonomuraea by Low Temperature Preservation - O. N. Sineva; N. G. Kulikova; S. N. Filippova; L. P. Terekhova (Антибиотики и Химиотерапия)
The influence of storage of actinobacteria Streptomyces hygroscopicus RIA 1433T, Nonomuraea roseoviolacea subsp. carminata INA 4281 and Nonomuraea sp. INA 34-06 at extremely low temperatures (-70°С) for 1.5 years was studied with respect to their viability and antibiotic activity. The spores of the actinobacteria preserved their high viability when freezed at a concentration of 105-107 CFU/ml. As for the antibiotic activity against the test culture Micrococcus luteus ATCC 9341, the strains differed: the S.hygroscopicus RIA 1433T colonies preserved their antibiotic activity against the test culture, the antibiotic activity of Nonomuraea roseoviolacea subsp. carminata lowered by 5% and that of N. sp. INA 34-06 lowered by 44%. Differences in the resistance of the strains to the storage at the extremely low temperatures were observed when the suspensions contained low concentrations of the spores (102 CFU/ml): S.hygroscopicus RIA 1433T preserved its viability and antibiotic activity during 1.5 years, while N.roseoviolacea subsp. carminata INA 4281 and N. sp. INA 34-06 lost the viability by the 8th month of the storage. The study showed that 10% glycerol solution used as a cryoprotector during the storage had no effect on viability and antibiotic activity of the actinobacteria.